THE ROLE OF PANCASILA AS THE NATION'S IDEOLOGY IN DEVELOPING EDUCATION IN FAVOR OF STUDENTS - Thoriq Abdul Aziz (Academic Solution Publisher, 2024)
This study aims to analyze the function of Pancasila ideology as the identity and entity of the nation and its role in creating education that favors students in the 21st century. The research method is a literature study of 30 journal articles relevant to the research. The results of the study show that 21st-century education not only develops academic aspects, but also character and morality. The Pancasila Student Profile is the foundation for character strengthening in the current learning process, implemented through the integration of Pancasila values in the daily life of students. Concrete efforts in curriculum design and learning processes that favor students demand critical, collaborative, and innovative thinking skills that prioritize Pancasila values. Thus, education that favors students not only creates academically superior generations, but also forms nationalist citizens who think globally while still prioritizing Pancasila values.